2008
DOI: 10.1197/jamia.m2744
|View full text |Cite
|
Sign up to set email alerts
|

Developing Informatics Tools and Strategies for Consumer-centered Health Communication

Abstract: As the emphasis on individuals' active partnership in health care grows, so does the public's need for effective, comprehensible consumer health resources. Consumer health informatics has the potential to provide frameworks and strategies for designing effective health communication tools that empower users and improve their health decisions. This article presents an overview of the consumer health informatics field, discusses promising approaches to supporting health communication, and identifies challenges p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
105
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(106 citation statements)
references
References 43 publications
0
105
0
1
Order By: Relevance
“…This was despite their exposure and access to medical staff who were available to pass on reliable information and promote insight into the condition. Keselman's study 9 reported that there is a need to draw on communication and social science theories of information to ensure better communication between health providers and clients. Interestingly, the mothers and communities appeared to have a better understanding of HIV/AIDS including the prevalence of the condition in children.…”
Section: Community Insights and Beliefs About Cancermentioning
confidence: 99%
“…This was despite their exposure and access to medical staff who were available to pass on reliable information and promote insight into the condition. Keselman's study 9 reported that there is a need to draw on communication and social science theories of information to ensure better communication between health providers and clients. Interestingly, the mothers and communities appeared to have a better understanding of HIV/AIDS including the prevalence of the condition in children.…”
Section: Community Insights and Beliefs About Cancermentioning
confidence: 99%
“…Moreover, it is an open access project. There are plans to add Open Access Collaborative Vocabulary developed by the CHVI to the UMLS at the US National Library of Medicine [39].…”
Section: Consumer Health Vocabularies (Chv)mentioning
confidence: 99%
“…The Internet has become an important medium to provide health information to lay users in order to empower them becoming actively involved in their own healthcare and to improve their health-related knowledge and decision making [1,2]. As older adults are significantly more at risk to suffer from chronic illnesses and other diseases [6,7], online health information is ideally positioned to support their wellbeing.…”
Section: Discussionmentioning
confidence: 99%
“…The Internet significantly changed the 'mechanics and economics' of health information for the broad population [1] and has become a major source of health information and decision support. The Internet allows presenting health information in more accessible ways, tailored to for specific audiences and provides anonymity in sensitive topics [2].…”
Section: Introductionmentioning
confidence: 99%